PERENCANAAN PENINGKATAN PELAYANAN PERPUSTAKAAN - Adhi Kristanto, Mr. (FIA UB, 2012)
Nowadays, the development of library tends to be routine agenda without a clearly defined objectives and the carried out activities are overlapping which lead to slow progress. As developing institution, library should have administrative planning which covers information sources, human resource, fund, infrastructure, system and facilities. So far library has not yet optimalized its function as place for exploring practical knowledge. The objectives of this research are, firstly, to describe and analyze the planning process on improving library service in Kantor Perpustakaan Umum dan Arsip Kota Malang. Secondly, to describe and analyze supporting and weakening factors for the library improvement planning in Kantor Perpustakaan Umum dan Arsip Kota Malang. The result of this research shows that Kantor Perpustakaan Umum dan Arsip Kota Malang used one news that stated Perpustakaan Kota Malang is the worst library in Indonesia as the strategic issue to gain support from local government and DPRD Kota Malang to develop the library. The planning steps and process have been in accordance with RPJMD Kota Malang and Renstra Kantor Perpustakaan Umum dan Arsip Kota Malang year 2009-2013. However, the head of the library has not involved stakeholders such as Section Head, Librarian and staff in planning process. The library service improvement planning program has not anticipated the fast development in society and information technology, hence, the programs tend to be stagnan. The supporting factors in service improvement planning are the regulation that supports the main task and function of Kantor Perpustakaan Umum dan Arsip Kota Malang in Pemerintah Kota Malangâs policy and planning as the reference of the planning, strategic location, and the community. The weakening factors are lack of commitment of Head of the Library to involve the Section Head, Librarian, and staff in planning, there is no service problem identification in planning, the resufle of Head of the Library, lack of fund to develop, low quality of human resources.